The weaner pig : nutrition and management (CABI, 2001)
The role of feed enzymes in the nutrition of the weaner pig is reviewed, focusing on main enzyme activities of carbohydrases, phytases and proteases. Current views on the modes of action and the potentially beneficial effects of these on young, newly weaned piglets is examined. The interaction between feed enzymes and the gut microflora, which is receiving increasing attention in current research involving novel microbiological techniques, and feed enzymes in weaner piglet nutrition is considered in the light of constraints on antibiotic use.